Infestation of Termite in Progeny Trial of Tecomella undulata - Meena, Desha; Bhatnagar, Shiwani; Singh, Anil (Indian Forester, 2016)
Termite damage is a serious problem in the establishment of forest plantations of many trees, as they have severely disrupted the ecological system and caused significant economic damage. They travel up through the roots into the trunk and branches and eventually disrupt the movement of nutrients and water through the vascular system resulting in wilting and drying of the tree. The study was conducted to assess the damage done by termites on Tecomella undulata field trial. At the age of five years, progenies attend an average height of 176cm and an average collar diameter of 2.57cm respectively. Results reveal the superficial infestation of termite upto the bark level ranging from 0.40m to 1.30m height of the trees during the long dry winter (October - February). For the management of termite infestation, an organophosphate insecticide Chlorpyrifos @1.5ml/litre was used with a repetition at an interval of one month. It was found that this dose could effectively control re-infestation of the termites for nearly five months.